Pengembangan Model Arsitektural Virtual Expo sebagai Media Alternatif Pembelajaran Kewirausahaan - Mutiara Cininta; Yohanes Priadi Wibisono (ATRIUM: Jurnal Arsitektur, 2023)
Title: Development of Virtual Expo Architectural Model as an Alternative Media for Entrepreneurship Learning   Participating in an exhibition plays a vital role in the learning process of entrepreneurship. Exhibitions can be a means to practice selling and introducing products or services, exploring competitor activities, dialogue and demonstrations with potential buyers, and establishing networks with distributors and investors. During the pandemic, there were limited exhibitions due to physical distancing. Although technological developments have made virtual expos possible, MSME players often need help to keep up with the ever-growing digital transformation. Therefore, entrepreneurship education should integrate digital literacy competencies to increase future generations' resilience. This research uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluate) development model. This study proposes a virtual expo model developed using SketchUp, Enscape, and Blender. Virtual Expo as a learning medium has feature criteria that allow participants to practice basic skills in entrepreneurship, including the ability to do promotions (pitching), formulate branding and marketing strategies, make prototypes, and present business plans. The metaverse-based prototype is more recommended for entrepreneurial learning media because it can facilitate real-time interactions such as presentations with visible cameras and gestures, booth designs displayed with three-dimensional models, and more interactive product presentations.